Grevillea robusta Delayed the Progression of Experimentally Induced Hepatic Fibrosis and Cirrhosis in Wistar Rats by Attenuating the Expression of Smooth Muscle Actin, Collagen, and TGF-β - Hameed, Saaid; Ur Rehman, Atta; Massey, Shazma; Syed, Nawazish-i-Husain; Anwar, Fareeha; Ahmed, Dildar; Ahmad, Sarfraz (Frontiers in Pharmacology, 2022)
The chronic damage to the liver causes fibrosis, especially when different proteins are accumulated in the liver, which is the basic characteristic of chronic liver damage. The excessive accumulation of the matrix protein such as collagen causes liver fibrosis. Liver fibrosis leads to cirrhosis, liver failure, and portal vein hypertension. Plants having antioxidants, free radical scavenging activities, and anti-inflammatory constituents are believed to be hepatoprotective in nature. Grevillea robusta (GR) is native to the subtropical environment. Its in vitro antioxidant, cytotoxic, and free radical scavenging activities are known, while the effect on liver fibrosis and cirrhosis remains elusive. The aim of this study was to evaluate the hepatoprotective and antifibrotic effects of Grevillea robusta plant. GR leaf extract (GREE) was prepared from the hydroethanolic extract (70%). Polyphenol and flavonoid contents and the in vitro antioxidant activity of the extract were determined. In vivo hepatitis was induced in Wistar rats by continual IP injections of CCl4. GREE was administered by oral gavage at a dose of 100, 300, and 500 mg/kg of body weight once daily for 4 weeks. Variations in rat’s body weight, liver-to-body weight ratio, serum alanine aminotransferases, gamma-glutamyltransferase, liver histology, and cellular markers of liver fibrosis were evaluated. Serum levels of alanine aminotransferase (ALT) (p < 0.05) and gamma-glutamyltransferase (γ-GT) (p < 0.001) were decreased in the treatment group compared with the disease control group. RBC count was increased (p < 0.001) in the treatment group compared with the disease control group. The expression of alpha-SMA was downregulated to 40% (p < 0.05) and that of collagen was decreased by 9% (p < 0.05) compared with the disease control group. Extracellular matrix deposition and necrotic areas were also decreased as compared to the disease control group. It can be concluded that GR possesses hepatoprotective action by virtue of antioxidant constituents and delays the progression of liver cirrhosis by suppressing the activation of extracellular matrix–producing cells in the liver.